Strategies and projects in the management of autoimmune dermatosis - Miranda Solis, Edwin Marcelo; Arellano Oleas , Yesenia Esthefania; Vallejo Bayas, Jessica Lisbeth (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Introduction: pemphigus vulgaris has been an autoimmune disease characterized by the formation of blisters on the skin and mucous membranes. Its diagnosis and management have represented a clinical challenge due to the variable presentation and potential severity. Therefore, the present study has focused on describing and analyzing the clinical presentation, diagnosis and treatment of pemphigus vulgaris. So that early diagnosis and proper management are emphasized to improve the prognosis of patients. Method: a review of recent scientific literature was conducted and case studies were analyzed to better understand the most effective diagnostic and therapeutic strategies. Modeling of the CRITIC and MOORA methods was even carried out in the selection of projects in the optimization of the management of pemphigus vulgaris. Results: it was identified that Nikolsky’s sign is crucial for clinical diagnosis, while skin biopsy with direct immunofluorescence is essential for histological confirmation. Treatment includes corticosteroids as a background, with additional immunosuppressants in refractory cases. Just as the selection of research projects has shown that the international clinical research network and predictive biomarker research have the highest potential in the hierarchy. Conclusions: the research highlights the imperative need for early diagnosis and an individualized therapeutic approach in the management of pemphigus vulgaris. This not only improves clinical response and reduces morbidity, but emphasizes the need for continuing medical education for the treatment of this disease.